PENINGKATAN LITERASI ARTIFICIAL INTELLIGENCE MAHASISWA MELALUI KEGIATAN KULIAH UMUM “AI FOR BUSINESS: TRANSFORMASI STRATEGI, INOVASI, DAN KEUNGGULAN KOMPETITIF DI ERA DIGITAL ” - Nabila Maisara; Wira Bharata (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The rapid advancement of Artificial Intelligence (AI) requires higher education institutions to equip students with relevant digital competencies. This article describes the implementation and evaluates the effectiveness of a public lecture entitled